Prevalence and associated body composition factors of sarcopenia in community-dwelling older adults - Boshi Wang; Chenyu Nong; Jiayu Zhang; Lihua Deng; Wei Li; Xue Zhang; Peng Liu (European Journal of Medical Research)
Abstract Background The objective of this investigation was to examine the frequency and determinants related to body composition of sarcopenia among aging individuals residing in the Beijing community through implementation of the diagnostic criteria for sarcopenia outlined by the 2019 Asian Working Group for Sarcopenia (AWGS). Methods A cross-sectional examination employing multistage cluster sampling was conducted on a sample consisting of 933 individuals aged 50 years or above. The study utilized the AWGS 2019 criteria for muscle mass, muscle strength, and physical function to gauge sarcopenia. In addition, data on demographic characteristics, anthropometry, and body composition were collected. Logistic regression analysis was carried out to ascertain the relationships between sarcopenia and correlated factors. Results The study found that the overall prevalence of sarcopenia was 8.3%. Sex (p < 0.001) and body mass index (BMI p < 0.001) were determined to have a significant association with the occurrence of sarcopenia. The adjusted analyses demonstrated that with each standard deviation increase in fat-free mass index (OR = 0.02 (0.01–0.05), of 95%), skeletal muscle mass (OR = 0.17 (0.12–0.25), of 95%), and other body composition indicators (including total body water 0.26 (0.2–0.35), intracellular water 0.1 (0.06–0.17), protein 0.01 (0–0.02), soft lean mass 0.35 (0.28–0.44), BMI 0.58 (0.51–0.67), body cell mass 0.21 (0.15–0.29), OR < 0.60, of 95%), the risk of sarcopenia decreased by more than 40%. Certain straightforwardly accessible anthropometric indices such as upper arm circumference (correlation coefficient 0.94 (0.9–0.97), 0.97 (0.95–1), 1.01 (0.99–1.03), respectively, of 95%), waist circumference (0.94(0.92–0.96), 1.01 (0.99–1.03), 1.02 (1–1.03), of 95%), hip circumference (0.93 (0.9–0.96), 0.99 (0.97–1.02), 1.02 (1–1.04), of 95%), waist-to-hip ratio (0.93 (0.87–1), 1.04 (1–1.08), 1 (0.97–1.03), of 95%), body fat percentage (1 (0.98–1.02), 1.02(1–1.04), 1.01 (0.99–1.02), of 95%), and phase angle (0.91 (0.89–0.93), 0.96 (0.94–0.98), 0.99 (0.98–1), of 95%) exhibited substantial correlation with skeletal muscle index, muscle strength or physical performance. However, no noteworthy link between sarcopenia and most variables associated with physical function was discovered. Conclusions The findings of the study highlight the prevalence of sarcopenia among the aging residents of Beijing. Certain easily measured anthropometric indices demonstrated strong correlation with muscle strength or physical performance, thereby providing an avenue for screening and diagnosing sarcopenia in older people who may not be able to undergo grip strength or physical function assessments. To investigate causal relationships, future studies employing longitudinal or interventional designs with a more comprehensive population are warranted.